A systematic review and meta-analysis of the effects of Entertainment-Education interventions on persuasive health outcomes - Anastasia Doré; Felix G. Rebitschek; Karolina Morello; Elena Stierstädter; Kyra J. Thiemann; Thomas Kubiak (Scientific Reports)
Abstract Entertainment-Education (EE) refers to the integration of entertaining and educational components within popular media, with the objective of positively impacting social and health behaviors. This study aims to synthesize the effects of EE for health communication. In particular, the effects of EE on health knowledge, intentions, attitudes, behavior, and self-efficacy were analyzed. Further, a persuasion index was created based on the primary outcomes. Only controlled or randomized-controlled studies were considered, and after screening, K = 39 of N = 4183 studies were included. Pairwise meta-analyses were conducted to determine the effects of EE on persuasive health outcomes. Additionally, potential effects of the subgroups delivery mode, gender, healthcare, type of control group and type and taxonomy of health behavior on a weighted persuasion index were analyzed. Analyses revealed evidence for significant small to moderate effects on all outcomes, with the largest effect sizes on knowledge and self-efficacy. Subgroups seem to account for a significant amount of heterogeneity, as a significant effect could be observed for all analyzed subgroups except for healthcare and gender. The meta-analysis suggests that EE is suitable for the communication of health messages, particularly when targeting prevention topics. However, it is imperative to exercise caution when interpreting the results, and further research is needed.